Relationship Between Facial Melasma and Ocular Photoaging Diseases - Lunla Udomwech; Chime Eden; Weeratian Tawanwongsri (Medical Sciences, 2025)
Background/Objectives: Facial melasma is a common, chronic, and relapsing hyperpigmentation disorder, affecting up to 40% of adult women in Southeast Asia. Although most cases are mild, the condition may have a considerable psychological impact. Ocular photoaging diseases are also common and have been increasingly recognized in aging populations exposed to chronic sunlight. Ultraviolet (UV) radiation is implicated in both melasma and ocular photoaging; however, their relationship remains unclear. Methods: This cross-sectional study investigated the association between facial melasma and UV-induced ocular conditions among 315 participants aged 30–80 years at Walailak University Hospital, Thailand. Facial melasma was diagnosed clinically and dermoscopically, with severity assessed using the modified Melasma Area Severity Index. Ophthalmological examinations evaluated UV-related ocular conditions, including pinguecula, pterygium, climatic droplet keratopathy, cataracts, and age-related macular degeneration. Logistic regression analyses were performed, adjusting for age, sex, and sun exposure. Results: Facial melasma was identified in 66.0% of participants (n = 208), and nuclear cataracts were significantly associated with melasma (adjusted odds ratio, 2.590; 95% confidence interval, 1.410–4.770; p = 0.002). Additionally, melasma severity correlated with nuclear cataract severity (ρ = 0.186, p = 0.001). Other ocular conditions were not significantly associated with melasma. Conclusions: These findings suggest a shared UV-related pathogenesis between facial melasma and nuclear cataracts. Sun protection measures, including regular sunscreen use, UV-blocking eyewear, and wide-brimmed hats, may help mitigate the risk of both conditions. Further multicenter studies are warranted to confirm these findings and explore the underlying mechanisms.